A Clinico-histopathological Diagnosis of Trichoadenomas on Nose: A Case report - Shrestha, Elisha; Pradhan, Namrata; Thapa, Diksha; KC, Sharnawi; Karn, Dharmendra (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Trichoadenoma of Nikolowski is a slow-growing, well-differentiated, rare, benign tumor closely resembling the infundibular portion of the hair follicle. Reporting such cases adds to the limited literature and helps clinicians better recognize and understand the condition. Due to its clinical and histopathological resemblance to other skin tumors, accurate diagnosis can be challenging. Reporting cases aids in refining diagnostic approaches. We report a case of a 51-year-old female with slow-growing skin-colored nodules over the tip of the nose and left nasal ala, with characteristic histopathological features suggestive of trichoadenoma.